Numerical Test Research on Loading Rate Effect of Rock Mass with Transfixion Sawtooth Structural Plane - Dongsong Li; Yanhong Du; Feng Chen; Tianhui Ma (Advances in Civil Engineering)
In this paper, numerical test research is carried out on the loading rate effect of a numerical specimen (sample C) with a transfixion sawtooth structural plane by using the rock failure process analysis (RFPA) 2D software. In order to study the mechanical characteristics difference between the rock mass with this kind of structural plane and other rock masses, the intact numerical specimen (sample A) of no structural plane and the numerical specimen (sample B) with smooth structural plane are also simulated. The uniaxial compression tests were carried out for each specimen under five loading rates of 0.002, 0.005, 0.008, 0.02, and 0.05 mm/s. The following several conclusions are obtained by the numerical test. When the loading rate is 0.002 or 0.005 mm/s, the failure mode of the numerical specimen C is an inclined linear fracture zone located in the middle and lower part of the rock mass; however, when the loading rate rises to 0.008, 0.02, and 0.05 mm/s, the fracture zone of the numerical specimen C is located in the middle and upper part of the rock mass, and its inclination angle is about 60 degrees. The peak strength, residual strength, and stress drop of the specimens A, B, and C increase with the addition of loading rate; the peak strength and stress drop of the sample C are higher than those of the other two samples. When the loading rate is 0.002 mm/s, the residual strength of sample C is lower than that of samples A and B, and the other four kinds of loading conditions are higher than those of specimens A and B. Based on the acoustic emission (AE) information, it can be seen that the failure modes of the numerical specimen C under five loading conditions are tensile failure. The AE accumulated energy decreases with the increase of loading rate, but the change law of AE accumulated number is opposite.